Estimating Quality in Home Advantage and Competitive Balance in the Portuguese Football League - Marques, António Cardoso (2019)
The issue of competitive balance is not normally considered in the study of home advantage. This paper focuses on home advantage, assessing and comparing it between seasons. The strength of the teams is estimated and linked with competitive balance. The results support that, in both the eighties and early nineties, the home advantage is more visible. After that, it tends to decrease. Meanwhile, competitive balance increases until the nineties and after that, the trend becomes unclear. The changes in the structure of the championship and the reward point system have affected the Portuguese league.